Current Status and Prospects of Ecological Restoration and Brownfield Reuse Research Based on Bibliometric Analysis: A Literature Review - Lin Zhang; Yuzhou Wang; Qi Ding; Yang Shi (Land)
Ecological restoration and brownfield reuse are important issues in the current field of urban sustainable development and environmental protection. This paper adopts bibliometric and network analysis methods, using more than 600 literature from Web of Science (WOS) and China National Knowledge Infrastructure (CNKI) databases as research objects, to analyze the research trends, main researchers, contributions of different disciplines, and research hotspots in ecological restoration and brownfield reuse. Based on the results of quantitative analysis, this paper reviews the main research theories, methods, and technologies of ecological restoration and brownfield reuse at home and abroad, as well as response strategies in different regions and future prospects under challenges. Among the top 10 disciplines in terms of disciplinary contribution, the discipline with the highest relevance in the research articles of CNKI is “Environmental Science and Technology”, accounting for approximately 47.24%. The discipline with the highest relevance in the research articles of WOS is “Building Science and Engineering”, accounting for approximately 61.21%. In terms of research theories and methods, emphasis is placed on the application of ecological engineering, landscape ecology, land economics, and sustainable development methods. At the same time, adaptive management methods are emphasized, aiming to achieve a balance between ecological protection and urban development. In terms of response strategies for different regions, the main strategies for ecological restoration and brownfield reuse are proposed from five main aspects: reducing soil erosion and controlling water pollution, restoring ecological communities and enhancing biodiversity, landscape reshaping and spatial transformation, tourism development, and leisure space design. Based on the current challenges in technology, law, funding, management, and society, research prospects for strengthening interdisciplinary integration, digital drive, interdisciplinary collaboration, and multi-party cooperation in the future are proposed. It can be seen that research in this field is no longer just a simple ecological issue, but a comprehensive social problem.